2017
DOI: 10.1172/jci92156
|View full text |Cite
|
Sign up to set email alerts
|

Photopharmacological control of bipolar cells restores visual function in blind mice

Abstract: Photopharmacological control of neuronal activity using synthetic photochromic ligands, or photoswitches, is a promising approach for restoring visual function in patients suffering from degenerative retinal diseases. Azobenzene photoswitches, such as AAQ and DENAQ, have been shown to restore the responses of retinal ganglion cells to light in mouse models of retinal degeneration but do not recapitulate native retinal signal processing. Here, we describe diethylamino-azo-diethylamino (DAD), a third-generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 70 publications
0
60
0
Order By: Relevance
“…Photo-pharmacology is an emerging field that uses drug molecules whose biological action can be controlled with light. [1] Prominent examples include photo-switchable ion-channel blockers to restore vision in mice, [2] a photo-switchable antidiabetic drug, glimepiride, to control insulin release, [1,3] and a photo-switchable capsaicin mimic as pain medicine. [4] An important class of photo-switchable compounds are photoswitchable lipids, synthetic lipid molecules that have an alkyl chain replaced by an azobenzene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-pharmacology is an emerging field that uses drug molecules whose biological action can be controlled with light. [1] Prominent examples include photo-switchable ion-channel blockers to restore vision in mice, [2] a photo-switchable antidiabetic drug, glimepiride, to control insulin release, [1,3] and a photo-switchable capsaicin mimic as pain medicine. [4] An important class of photo-switchable compounds are photoswitchable lipids, synthetic lipid molecules that have an alkyl chain replaced by an azobenzene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…14 Newer-generation compounds feature long half-lives (on the orders of weeks) 15 and activation of upstream cellular components such as bipolar cells. 16 Advantages of this approach include the need only for small-molecule treatment (in the 1-component system), the reversibility or upgradability of compounds (whereby the optimal agent and its dosing could be titrated for the individual), and a more familiar small-molecule Food and Drug Administration approval path. Challenges include maintaining continuous delivery and open questions on long-term toxicity.…”
Section: Photopharmacologymentioning
confidence: 99%
“…Additional benefits, besides their large geometrical change, include reversibility of 10 5 to 10 6 cycles without detectable photodegradation or loss of responsiveness, synthetic accessibility via Mills reaction, oxidative/reductive coupling or azo coupling, and tunability of their photochromic properties . Furthermore, azobenzene‐based photoresponsive systems have already been successfully applied in several biological systems . Recently, the research groups of Wijtmans and Leurs reported the use of a bidirectional photoswitchable antagonist toolbox for the H 3 R, a GPCR, based on azobenzene …”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Furthermore, azobenzene-based photoresponsive systems have already been successfully appliedi ns everal biological systems. [37][38][39][40][41] Recently,t he research groups of Wijtmans and Leurs reported the use of ab idirectional photoswitchable antagonist toolbox for the H 3 R, aG PCR, based on azobenzene. [16] We designed ap hotochromic antagonist for the H 1 Rb ased on azobenzene as the photochromic scaffold.…”
Section: Introductionmentioning
confidence: 99%